Women’s quest for home: spatial imaginary in Kazuo Ishiguro’s a pale view of hills - Ling, Xu; Awang, Mohammad Ewan; Singh, Hardev Kaur Jujar (International Islamic University Malaysia, 2024)
Unhomely homes have been a recurring theme in Kazuo Ishiguro’s novels, and his debut novel, A Pale View of Hills (1982), is no exception. While previous research has primarily focused on themes such as displacement, alienation, and trauma in the novel, limited attention has been given to exploring the social-spatial and gendered spatial factors contributing to this sense of homelessness. This paper examines the meanings of home in A Pale View of Hills by drawing upon Blunt’s and Dowling’s concept of home as a spatial imaginary. It argues that the idea of home in the post-war Japanese discourse is actively challenged and reshaped by the female characters in Ishiguro’s novel. This dynamic process encompasses three facets: materially, it includes the destruction of homes, the Westernisation of domestic space, and gendered space and domesticity; imaginatively, it involves long-lasting trauma and repression; and relationally, it signifies the transformation of home from unhomely to a homely one. This paper aims to provide a spatialised and politicised understanding of home in A Pale View of Hills, fostering a more dynamic view of women’s identity construction.